The Decision Support System Uses the Preference Selection Index Method in Determining Healthy Cooperatives - Sulistiani, Heni; Maryana, Sufiatul; Palupiningsih, Pritasari; Mehta, Abhishek (PDSI, 2023)
Determining a healthy cooperative is a challenge that requires attention to several key aspects. Effective management, stable finances, active member involvement, and compliance with laws and regulations are key factors to be considered. By paying attention to all these factors and taking appropriate action, the cooperative can achieve optimal health levels and make a significant contribution to its members as well as the surrounding community. This study aims to determine healthy cooperatives using the Preference Selection Index (PSI) method in determining the best healthy cooperatives using the criteria of Capital, Quality of Productive Assets, Management, Efficiency, Liquidity, Independence, and Cooperative Identity so that the results of the best healthy cooperative ranking recommendations will be able to become recommendations for a decision. Based on the results of the calculation of the final value and ranking of the best healthy cooperatives using the PSI method, rank 1 is Koperasi-02 with a final value of 0.10737, rank 2 is Koperasi-01 with a final value of 0.10029, rank 3 is Koperasi-03 with a final value of 0.05223, rank 4 is Koperasi-04 with a final value of 0.0107. The results of testing using blackbox testing that has been carried out obtained the results of the number of answers from respondents have a value of 100% in accordance with testing the functionality of the system using blackbox testing